Pendampingan Implementasi Pendidikan Karakter di Era Globalisasi - Andryadi Andryadi; Baili Baili; Verawati Ardilla (Sejahtera: Jurnal Inspirasi Mengabdi Untuk Negeri, 2025)
Character education that teaches moral values, ethics, and positive attitudes must be applied early in the learning process to form individuals who are not only academically intelligent, but also have integrity and social responsibility. The purpose of this study is to provide assistance to teachers in implementing character education amid the challenges of the globalization era. In addition. The research was conducted in Candi Village, Tanah Sepenggal Sub district, Bungo District, Jambi Province, involving the teachers' assembly. The results showed that the mentoring successfully improved teachers' understanding and readiness to implement character education. About 90% of the teachers involved reported improvements in their understanding of the basic principles of character education and ability to integrate them in learning. The implications are therefore important for the development of character education in Indonesia, especially in facing the challenges of globalization. Continued assistance to teachers is expected to strengthen the implementation of character education at all levels of education.